Raja Kecil Pendiri Kerajaan Siak Sri Indrapura (Jurnal Ilmu-Ilmu Sejarah, Budaya Dan Sosial ( LENTERA ), 2009)
The aim of the research is to find out how Siak Sri IndrapuraPalace was existed by Raja Kecil in 1723 at Buantan. The method used inthis research is library research by comparing two Malay literatures, Tuhfatal Nafis holy book and Siak war poem. The result of this research is toprove that Raja Kecil is Raja Malakas generation. Who finally bmlt Siak SriIndrapura Palace after they were not able to defend their autliority in Malaka.Keywords : Raja Kecil, Siak Sri Indrapu